The Cold War in the Classroom International Perspectives on Textbooks and Memory Practices - Christophe, Barbara; Gautschi, Peter; Thorp, Robert (Palgrave Studies in Educational Media, 2019)
This book is open access under a CC BY 4.0 license. This book explores how the socially disputed period of the Cold War is remembered in today's history classroom. Applying a diverse set of methodological strategies, the authors map the dividing lines in and between memory cultures across the globe, paying special attention to the impact the crisis-driven age of our present has on images of the past. Authors analysing educational media point to ambivalence, vagueness and contradictions in textbook narratives understood to be echoes of societal and academic controversies. Others focus on teachers and the history classroom, showing how unresolved political issues create tensions in history education. They render visible how teachers struggle to handle these challenges by pretending that what they do is 'just history'. The contributions to this book unveil how teachers, backgrounding the political inherent in all memory practices, often nourish the illusion that the history in which they are engaged is all about addressing the past with a reflexive and disciplined approach.